Implementasi ISO 27001 dalam Meningkatkan Kepercayaan Pengguna dalam Sektor Industri: Penelitian - Pia Suci Lestari; Fatimah Zahra Tambunan; Ariq Wiratama Nasution; Monika Amelia Manurung; Ropika; Cherine Lita Purnama Panjaitan; Dear Selvanathan Sinaga (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study analyzes the challenges and strategies for implementing ISO 31000: The implementation of ISO 27001 in the financial sector has been proven to improve information security and user trust. A literature review of nine journals shows that this standard is effective in managing risks, complying with regulations, and implementing security controls such as encryption and multi-factor authentication. Some institutions have reported a reduction in security incidents of up to 40%. However, implementation challenges include limited human resources and a lack of user evaluation user perception. These findings underscore the role of ISO 27001 as a critical standard for building trust in the digital age.